2019
DOI: 10.1002/jemt.23253
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of reciprocating systems for removing root filling material plus complementary cleaning methods in flattened canals: Microtomography and scanning electron microscopy study

Abstract: The aim of this study was to evaluate three reciprocating systems and complementary cleaning methods on filling material removal during retreatment of flattened canals. Thirty-six mandibular incisors were prepared using rotary instruments up to size 25.08 and filled using the single-cone technique. Subsequently, the teeth were divided into three groups (n = 12) according to retreatment procedures: Reciproc Blue (RB): 25/0.08 and 40/0.06; ProDesign R (PDR): 25/0.06 and 35/0.05; and WaveOne Gold (WOG): 25/0.07 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
1
20
0
4
Order By: Relevance
“…An increased enlargement of apical re-preparation has been associated with a lower volume of residual filling materials [ 7 , 10 , 12 ]. This difference has been reported between additional instrumentation with larger tip sizes (size 35–40) compared to size 25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased enlargement of apical re-preparation has been associated with a lower volume of residual filling materials [ 7 , 10 , 12 ]. This difference has been reported between additional instrumentation with larger tip sizes (size 35–40) compared to size 25.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for cleaning and disinfection will essentially depend on either supplementary approaches or enlargement to even larger sizes [ 1 , 2 , 3 , 4 ]. Adjunctive procedures show controversial outcomes and still do not enable the thorough cleaning of root canals [ 5 , 6 , 7 , 8 , 9 , 10 ]. Using a larger preparation size would be expected to result in fewer unprepared areas and, consequently, a higher volume of old filling material removal, optimizing disinfection [ 7 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to evaluate different removal procedure techniques of the root canal and all are unanimous that no method is able to completely filling material remove (5,8,11). These results corroborate with the data obtained in the present study in which, regardless of the kinematics and characteristics of the instruments used, all presented residual filling material (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…Reciproc (VDW GmbH, Munich, Germany) was one of the first reciprocating systems to be used in root canal shaping, however, several studies have also demonstrated its efficiency in endodontic retreatment (5,10). In order to further improve the mechanical properties, the Reciproc suffered a process of heating/cooling giving rise instruments Reciproc Blue (VDW GmbH, Munich, Germany) which have a NiTi alloy with blue technology (5,11). These instruments have been the subject of studies that point to a greater resistance to cyclic fatigue than their predecessor (12)(13) and also show to be efficient in endodontic retreatment (5,11…”
Section: Introductionmentioning
confidence: 99%